The The Fulfillment Of Citizenship Rights For The Children Of Indonesian Migrant Workers Who Are Working Illegally In Malaysia - Yogi Prabowo; Wicipto Setiadi; Ahmad Ahsin Thohari (Al-Makki Publisher, 2024)
The right to citizenship is a fundamental right for every human being. However, there are still individuals who have not been able to access their citizenship rights, namely the children of Indonesian migrant workers who are working illegally in Malaysia. The author wants to know about the protection of citizenship rights for the children of Indonesian migrant workers who work illegally in Malaysia, as well as the state's responsibility in fulfilling the citizenship rights of these children. This research used a qualitative normative method. It relied on literature and written sources for data. The results indicate that the children of Indonesian migrant workers who work illegally in Malaysia, according to principles and applicable laws, are Indonesian citizens. However, they do not have documents to prove their citizenship. The Indonesian government has a responsibility to ensure the possession of citizenship documents for the children of Indonesian migrant workers who work illegally in Malaysia.